2014
DOI: 10.5532/kjafm.2014.16.4.343
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Emergence Model of Southern Type Garlic Based on Temperature

Abstract: We developed a simple model to predict emergence time and emergence rate of southern type garlic using the daily mean temperature. Emergence rate of garlic was decreased and emergence time was delayed on higher temperature than optimum temperature of 12.7 o C. In the model, firstly daily emergence rate was calculated using a beta function to input daily mean temperature, then the percentage of garlic emergence was calculated using a nonlinear model with accumulated emergence rate. The model was good to describ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
1
0
Order By: Relevance
“…Previous studies have used high pressure sodium lamps or infrared lamps, and some reported various plant growths, although the crops were different (Moon et al, 2014;Graper and Healy, 1991). As such, it was revealed that supple- Table 3.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have used high pressure sodium lamps or infrared lamps, and some reported various plant growths, although the crops were different (Moon et al, 2014;Graper and Healy, 1991). As such, it was revealed that supple- Table 3.…”
Section: Discussionmentioning
confidence: 99%
“…Mineral nutrient content in the bulbs of southern-type garlic (Allium sativum L.) grown for 265 days in different culture temperatures in a temperature gradient tunnel 온도구배터널 내 생육온도 상승에 따른 난지형 마늘의 지상부 생장, 인경 발달 및 무기성분 함량의 변화 고 찰 마늘의 인경 발달은 인편에서 맹아의 출현, 잎의 발달과 같은 초기 영양생장, 인경의 형성과 발달, 그리고 성숙 단계로 구분되 며(del Pozo and González, 2005), 각 단계에는 온도가 중요하게 작용한다. 인편으로부터 맹아의 출현은 온도에 민감하여 10°C에서는 100% 출현하는 데 반해 고온으로 갈수록 출현율이 저조하여 30°C에서는 75%로 감소하고, 출현율이 50%에 도 달하는 데 소요되는 시간도 온도가 증가할수록 늦어지는 것으로 보고된 바 있다(Moon et al, 2014). 또한, 마늘 재배 시 기후변 화 시나리오 RCP 4.5와 RCP 8.5를 적용하였을 때 기온이 상승하면 마늘의 파종 적기는 늦어지고 수확 적기는 빨라져 추후 100년 동안 재배기간이 50 -90일 정도 짧아질 수 있다고 한다(Park et al, 2018).본 연구에서도Fig.…”
unclassified